2009
DOI: 10.1007/s11434-009-0380-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic voltammetry, convolutive voltammetry, chronopotentiometry and digital simulation studies of [Pt(C≡C tol)2(dppm)2Ir(CO)2]+PF− 6 complex

Abstract: Citation: El-Hallag S I. Cyclic voltammetry, convolutive voltammetry, chrono-potentiometry and digital simulation studies of [Pt(C C ≡ tol) 2 (dppm) 2 Ir(CO) 2 ] + PF − 6 complex.The electrochemical behaviour of the heterobimetallic complex [Pt(C≡C tol) 2 (dppm) 2 -Ir(CO) 2 ] + PF − 6 was studied via cyclic voltammetry, convolutive voltammetry and chronopotentiometry at glassy carbon electrode in dichloromethane solution. The electrochemical parameters calculated from experimental data were tested and confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It was indicated that the complete chemical process consists of the electrochemical reaction on the electrode surface and the subsequent irreversible reaction. [37] In order to detect the electrochemical stability of the prepared electrode in alkaline solution, 10 % Ni-MOF-74/CPE was scanned for 100 cycles in 0.10 M NaOH solution, and the 11th, 51st and 100th cycle were plotted (Figure S8). No significant change in the height of the redox peaks was observed in the cyclic voltammetry.…”
Section: Electrocatalytic Properties Of Methanol Oxidation Over Ni-mof-74/cpementioning
confidence: 99%
“…It was indicated that the complete chemical process consists of the electrochemical reaction on the electrode surface and the subsequent irreversible reaction. [37] In order to detect the electrochemical stability of the prepared electrode in alkaline solution, 10 % Ni-MOF-74/CPE was scanned for 100 cycles in 0.10 M NaOH solution, and the 11th, 51st and 100th cycle were plotted (Figure S8). No significant change in the height of the redox peaks was observed in the cyclic voltammetry.…”
Section: Electrocatalytic Properties Of Methanol Oxidation Over Ni-mof-74/cpementioning
confidence: 99%